Penerapan Data Mining Untuk Memprediksi Prestasi Siswa SMA Pada Dinas Pendidikan Provinsi Jambi - Lastari, Widya; Jasmir, Jasmir (LPPM Universitas Dinamika Bangsa, 2023)
The implementation of education is one of the important efforts in improving the quality of students. With good education it will be useful in realizing the goals of students. This study utilizes data mining techniques using yahoo K-Nearest Neighbor (K-NN) to predict student achievement. The attributes used in this study are scores: Indonesian, Mathematics, English, Biology, Chemistry, Physics, Sociology, Economics, Geography and the target is the study of students. From the results of the study, the best results were at K = 3, the use of python sklean data mining got an accuracy value 61.9% and error MSE 0.8 by comparison Naive Baiyes with accuracy 58% and error MSE 0.41 , and for Rapid miners using KNN got value accucary51%.